Development of Tea Plantation Agro-Tourism in Tarumajaya Village, Kertasari - Adhitya M. Maheswara; Indrati Asyariri; Lia Amelia Nurkhazanah; Syifa Fatimazzahroh (Universitas AMIKOM Yogyakarta, 2026)
Tarumajaya Village is a tea plantation area with significant potential in the agro-tourism sector. Geographically, the village is surrounded by vast tea plantations jointly managed by PT Perkebunan Nusantara VIII, Perum Perhutani, and PT London Sumatra Indonesia. In addition to the tea plantations, the area is also home to a natural lake called Situ Cisanti, which has a circumference of approximately three kilometers and serves as one of the main water sources of the Citarum River.Considering these potentials, Tarumajaya Village could be developed into a leading agro-tourism destination similar to the Osulloc Tea Museum tea plantation tourism area on Jeju Island. Furthermore, this tourism potential is supported by local MSME communities under Bale Kertasari, which produce various traditional food and beverage products unique to the village. In this context, the utilization of the Korean language becomes an innovative strategy to support the marketing of local MSME products through labels, packaging, and culturally based promotional narratives. By developing foreign language skills relevant to potential markets, particularly South Korean tourists, Tarumajaya’s MSME products can become more attractive and value-added, while also gaining greater opportunities to penetrate international markets and strengthen the identity of the village as a globally competitive tourism destination.